ANALISIS KINERJA KEUANGAN MENGGUNAKAN METODE ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED (Studi Kasus Pada Perusahaan Pertambangan Sektor Logam dan Mineral yang Terdapat di BEI) - Salsa Zahra Fatimah; Dewi Sartika (Media Bina Ilmiah, 2024)
Assessment of financial performance can generally be done using several financial analysis tools, but the problem that occurs is that there is no optimal ratio for shareholders to maximize their wealth. Aim of this research is to measure and assess the financial performance of mining companies in the metal and mineral sub-sector listed on the Indonesia Stock Exchange for the 2020-2022 period using the Economic Value Added (EVA) and Market Value Added (MVA) methods. This research uses a quantitative descriptive method using secondary data in the form of IHSG financial reports, BI interest rates, and share prices of mining companies in the metal and mineral sub-sector listed on Indonesia Stock Exchange (BEI) for the 2020-2022 period. Results of this research known that each company (ANTM, CITA, IFSH, and TINS) fluctuates in 2020-2022, each company has a positive EVA value. Meanwhile, the market value of shares or MVA in metal and mineral companies (ANTM, CITA. IFSH, and TINS) each company provides substantial wealth for shareholders. This is shown by the positive MVA value during the research period in 2020-2022 respectively.